Severe COVID-19 Is Associated With an Altered Upper Respiratory Tract Microbiome - Shilts, Meghan H.; Rosas-Salazar, Christian; Strickland, Britton A.; Kimura, Kyle S.; Asad, Mohammad; Sehanobish, Esha; Freeman, Michael H.; Wessinger, Bronson C.; Gupta, Veerain; Brown, Hunter M.; Boone, Helen H.; Patel, Viraj; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Background: The upper respiratory tract (URT) is the portal of entry of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV-2 likely interacts with the URT microbiome. However, understanding of associations between the URT microbiome and severity of coronavirus disease 19 (COVID-19) is still limited. Objective: Our primary objective was to identify URT microbiome signature/s that consistently changed over a spectrum of COVID-19 severity. Methods: Using data from 103 adult participants from two cities in the United States, we compared bacterial load and the URT microbiome between 5 groups: 20 asymptomatic SARS-CoV-2 negative participants, 27 participants with mild COVID-19, 28 participants with moderate COVID-19, 15 hospitalized patients with severe COVID-19, and 13 hospitalized patients in the ICU with very severe COVID-19. Results: URT bacterial load, bacterial richness, and within-group microbiome composition dissimilarity consistently increased as COVID-19 severity increased, while the relative abundance of an amplicon sequence variant (ASV), Corynebacterium_unclassified.ASV0002, consistently decreased as COVID-19 severity increased. Conclusions: We observed the URT microbiome composition significantly changed as COVID-19 severity increased. The URT microbiome could potentially predict which patients may be more likely to progress to severe disease or be modified to decrease severity. However, further research in additional longitudinal cohorts is needed to better understand how the microbiome affects COVID-19 severity.